Carlos Aldao's translations: Argentine cultural nationalism and the politics of history. (2nd October 2021) - Davies, Catherine
ABSTRACT: This article discusses the translation objectives, strategy and praxis adopted by Argentine Carlos Agustín Aldao (1860–1932) in his translations to Spanish of British travel accounts published by travellers to the River Plate in the early nineteenth-century. The article considers the immediate social, cultural and political context of the translations, first published in Buenos Aires between 1916 and 1921, and relates this case study to broader questions such as how translation might be used to acquire and exercise power in public life, and whether translation can intervene in the politics of history. Ultimately, within the framework of Argentine-British relations, the article examines the ethics of Aldao's translation choices and the extent to which his translations may be considered acts of nation-building and decolonisation.